An analysis of the Cordylus Polyzonus complex (Reptilia : Cordylidae) in the South-Western Cape - Badenhorst, N. C. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 1990.